2015
DOI: 10.1007/s00198-015-3318-4
|View full text |Cite
|
Sign up to set email alerts
|

Opportunistic screening for osteoporosis using the sagittal reconstruction from routine abdominal CT for combined assessment of vertebral fractures and density

Abstract: Assessment of the sagittal view alone at routine abdominal CT for both vertebral fractures and trabecular bone mineral density provides a rapid and effective opportunistic screen for detecting individuals at increased risk for fragility fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
103
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 164 publications
(117 citation statements)
references
References 20 publications
5
103
0
Order By: Relevance
“…(6) Previous work has shown that CT scans obtained for other indications can be used to assess BMD at the spine and may provide an acceptable initial screen. (7)(8)(9)(10) Although these CT vertebral measures can be used to identify those at highest risk for fracture, none provide 10-year fracture risk, which can truly guide when further workup and treatment is indicated.…”
Section: Introductionmentioning
confidence: 99%
“…(6) Previous work has shown that CT scans obtained for other indications can be used to assess BMD at the spine and may provide an acceptable initial screen. (7)(8)(9)(10) Although these CT vertebral measures can be used to identify those at highest risk for fracture, none provide 10-year fracture risk, which can truly guide when further workup and treatment is indicated.…”
Section: Introductionmentioning
confidence: 99%
“…Other imaging modalities that capture tissue densities include CT scans which measure signal attenuation in the form of Hounsfield units (46). Several studies have successfully correlated CT HUs to bone density for clinical applications (47)(48)(49)(50)(51)(52)(53)(54)(55).…”
mentioning
confidence: 99%
“…Although the obtained CT image also depends on the absorption of X‐radiation, in contrast to DEXA a 3D replication of the scanned object is produced using a standardized linear attenuation coefficient scale, where air is defined as −1,000 and water as 0, expressed in HU. Also, in human medicine, the use of CT scans obtained for other indications (e.g., CT colonography) to determine bone density is of high interest in current research . All these studies have in common the fact that the HU of a defined 2D region of interest (ROI) is measured in a single or in multiple slice(s).…”
mentioning
confidence: 99%
“…Measuring bone density with computed tomography instead of using dual-energy X-ray absorptiometry (DEXA) has become a focus of interest in the last few years in human and veterinary medicine. [1][2][3][4][5][6][7][8][9][10][11][12][13] However, according to the World Health Organization, the gold standard for quantitative measurements of bone density is dual-energy X-ray absorptiometry (DEXA). 14,15 Both modalities (DEXA and CT) are based on X-radiation.…”
mentioning
confidence: 99%
See 1 more Smart Citation